Barkhī-i rahnamūd̓h-a barā-yi kārmandān-i -idi̓ūlūzk-ik-i Jabhah-i Mill-i-i Pidar-i Vaṭan - Farīvar, Farīdūn (Shumārah-i musalsal 4., 1980)
Guidelines for members of the Jabhah-i Mill-i-i Pidar-i Vaṭan, an organization for spreading the ideology of the communist government among the people of Afghanistan.